Toll-like receptor 9 (TLR-9) promotor polymorphisms and gene expression are associated with persistent Staphylococcus aureus nasal carriage - Nurjadi, Dennis; Heeg, Klaus; Weber, A. N. R.; Zanger, Philipp (Clinical microbiology and infection, 2018)
Objectives - Toll-like receptor (TLR) 9 could have importance in human Staphylococcus aureus immunity, but population-level evidence for this hypothesis is missing. - Methods - We phenotyped S. aureus nasal carriage of 603 volunteers using four consecutive swabs, genotyped TLR9 promotor variants in 106 persistent carriers and 219 noncarriers, measured TLR9-mRNA expression in whole blood after stimulation with viable S. aureus and studied mutual associations of carriage, transcriptional activity and single nucleotide polymorphisms while accounting for sex and hormone contraceptive use (HCU). - Results - The −1486 (rs187084) and −1237 (rs5743836) CT haplotype was more common in noncarriers (185/438, 42%) than in carriers (63/212, 30%), with the TT haplotype showing a reverse association (noncarriers, 180/438, 41%; carriers 117/212, 55%) (χ2 p 0.001). Mean TLR9 mRNA expression in whole blood was higher in noncarriers (ratiocarriers/noncarriers 0.63; 95% confidence interval, 0.43-0.92; p 0.017). A duplication of TLR9 transcriptional activity lowered the odds of persistent S. aureus carriage by 37% in the overall group (odds ratio = 0.63; 95% confidence interval, 0.42-0.94; p 0.022) and by 54% in women (odds ratio = 0.46; 95% confidence interval, 0.23-0.90; p 0.023). Promotor haplotype and HCU had a combined effect on TLR9 transcription (interaction model): women in the TT (risk) haplotype/HCU− stratum (baseline) had lower mRNA levels than women in the CT (protective) haplotype/HCU− (ratio 1.92; p 0.055), the CT haplotype/HCU+ (ratio 2.02; p 0.032) and the TT haplotype/HCU+ (ratio 2.59; p < 0.004) strata. No such associations were observed in men. - Conclusions - We provide evidence that TLR9 affects human S. aureus immunity and present potential explanations for differences according to sex in S. aureus colonization and infection.